Validación del proceso de manufactura de una forma farmacéutica en suspensión en laboratorios Remo S.A.S (2018)
The validation of the manufacturing process of the Finoxal Suspension product was carried out with the support of Laboratorios Remo S.A.S in the city of Bogotá to comply with the requirements of resolution 1160/16 of the Ministry of Health and Social Protection. It was also carried out following the guidelines provided by the FDA (Food and Drug Admissibility) and the WHO (World Health Organization). To carry out the diagnosis of the manufacturing process of the product, the existing documentation was reviewed, inquiring information pertinent to the master formula, train of equipment and quality attributes of the finished product. According to the guidelines given by the Good Manufacturing Practices, the necessary corrective actions were established to begin the validation process. For the realization of the retrospective validation, the manufacturing stages and the final chemical and physical characteristics of each product were analyzed. These last ones give account of the intrinsic variability to which a process of elaboration is subject, reason why the statistical control of them, will allow to have a statistical control of the process of in himself. The results showed that the manufacturing process is constant over time and that the existing interlote variability is not significant. The validation protocol was carried out and it was executed obtaining the necessary results for the validation analysis of the productive process. This paper is useful when analyzed from the perspective of being a contribution to the implementation of this type of validation as a new work tool for the company, considering that it is a simple, economical and useful methodology in the continuous improvement of the quality specifications.